The Effect Of Solvability, Profitability, Dividend Policy, And Company Value On Stock Returns - Layly Dwi Rohmatunnisa (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Study This aiming For know and analyze influence solvability , profitability , policy dividends , and value company to stock returns on companies property and real estate listed on the IDX for the 2017-2021 period . Population study is company property and real estate listed on the IDX for the 2017-2021 period . Selection sample study use method purposive sampling and obtained 9 companies that meet the requirements criteria . Testing hypothesis use analysis multiple linear regression . Research results show solvability , profitability , policy dividends , and value company No influential to stock returns.